ANALYSIS OF THE EFFICIENCY IN PRODUCTION OF TOMATOES AMONG AGRICULTURAL ESTABLISHMENTS: DATA ENVELOPMENT ANALYSIS AND STOCHASTIC FRONTIER ANALYSIS - Patson SHIIKABA; Mehmet Arif ŞAHİNLİ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Technical efficiency of tomato producers in Ankara was evaluated using Data Envelopment Analysis and Stochastic Production Frontier methods. Using Stratified Random Sampling method 77 tomato producers were selected and structured questionnaire was used to collect data from the selected farmers. The main tomato production problems faced by tomato producers are diseases representing 22.4%, low labour force 20.0%, cost of inputs 17.7% and access to irrigation water 1.9%. The main marketing problems faced by farmers are transportation cost of tomatoes to sales point %39.9 and low selling of tomatoes 38.6%. Technical efficiency was found to be 55.55% under stochastic production frontier while under Data Envelopment Analysis was found to be 86.43%. Stochastic Frontier Analysis separates causes of changes in output into managerial and chance hence lower efficiency score compared to data envelopment analysis approach which does not. The results of Stochastic Production Frontier indicate that all factors of production that include labour, land, seedling, animal manure, chemical fertilizer, pesticides, irrigation and tractor expenditure where all found to be statistically significant in influencing production on the other hand formal education of the farmer, use of agricultural credit and membership to agricultural organisation were found to be statistically significant in influencing technical efficiency scores.